Mirror therapy for phantom limb pain: Brain changes and the role of body representation. (10th December 2013) - Foell, J.; Bekrater‐Bodmann, R.; Diers, M.; Flor, H.
Abstract Background Phantom limb pain (PLP) is a common consequence of amputation and is difficult to treat. Mirror therapy (MT), a procedure utilizing the visual recreation of movement of a lost limb by moving the intact limb in front of a mirror, has been shown to be effective in reducing PLP. However, the neural correlates of this effect are not known. Methods We investigated the effects of daily mirror training over 4 weeks in 13 chronic PLP patients after unilateral arm amputation. Eleven participants performed hand and lip movements during a functional magnetic resonance imaging (fMRI) measurement before and after MT. The location of neural activity in primary somatosensory cortex during these tasks was used to assess brain changes related to treatment. Results The treatment caused a significant reduction of PLP (average decrease of 27%). Treatment effects were predicted by a telescopic distortion of the phantom, with those patients who experienced a telescope profiting less from treatment. fMRI data analyses revealed a relationship between change in pain after MT and a reversal of dysfunctional cortical reorganization in primary somatosensory cortex. Pain reduction after mirror training was also related to a decrease of activity in the inferior parietal cortex (IPC). Conclusions Experienced body appearance seems to be an important predictor of mirror treatment effectiveness. Maladaptive changes in cortical organization are reversed during mirror treatment, which also alters activity in the IPC, a region involved in painful perceptions and in the perceived relatedness to an observed limb.